PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII E SMP NEGERI 18 PALU PADA MATERI KESEBANGUNAN SEGITIGA - Dhini Syafitri; I Nyoman Murdiana; Mubarik Mubarik; Ibnu Hadjar (Universitas Tadulako, 2025)
This research aims to obtain a description of the application of the model Problem Based Learning in differentiated learning to improve the learning outcomes of class VII E students at SMP Negeri 18 Palu on triangle congruence material. This type of research is Classroom Action Research (CAR) with reference to the research design of Kemmis and Mc. Taggart, namely 1) planning, 2) implementing actions, 3) observation, and 4) reflection. The subjects in this research were 22 students in class VII E of SMP Negeri 18 Palu and 3 students were selected as informants. Data collection techniques are observation, tests, interviews and field notes. This research consists of two cycles with two meetings in each cycle which follow the PBL learning steps in differentiated learning in the phase of organizing students to learn and the phase of guiding individual and group investigations. In the phase of organizing students to learn, the teacher groups students based on academic mapping, namely (1) category 1 group (comprehensive understanding), students who understand the material completely, (2) category 2 (partially understanding), students who understand most of the material and (3) category 3 group (limited understanding), students who show very limited understanding of the material. Meanwhile, in the phase of guiding individual and group investigations, the teacher guides each group with different treatment, namely (1) category 1 group (comprehensive understanding), the teacher provides a little guidance to search for information independently because they are deemed to have been able to solve the problem given. (2) category 2 group (partially understanding), the teacher provides guidance but still leaves room for students to find their own solutions, and (3) category 3 group (limited understand), the teacherguides directly to direct students in searching for information. In cycle I the number of students who completed was 12 students with a completion percentage of 54.5% and in cycle II the number of students who completed was 18 students with a completion percentage of 81.8%. The results of observing teacher activities were in the good category with a value in the first cycle of 84% and an increase in the second cycle of 95%. The results of observing student activities in cycle I were 73% and in cycle II there was an increase of 93%. The average score in the final action test in cycle I was 68% and increased in cycle II, namely 80.7%. Based on the research results, it can be concluded that the implementation of the model Problem Based Learning in differentiated learning can improve the learning outcomes of class VII E students at SMP Negeri 18 Palu on the material of triangle similarity.